MANAJEMEN SARANA DAN PRASARANA PROGRAM MAGISTER FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS ISLAM NEGERI SUNAN KALIJAGA YOGYAKARTA MENUJU WORLD CLASS UNIVERSITY (WCU) - Indah Puspa Haji; Riski Angga Putra (Jurnal Al-Hikam, 2024)
UIN Sunan Kalijaga Yogyakarta is one of the best universities in Indonesia which continuously strives to improve its quality so that it is in line with the best higher education institutions in the world. The State Islamic University of Sunan Kalijaga Yogyakarta has made various efforts in implementing various things towards World Class University (WCU). The Master Program of the Faculty of Tarbiyah and Teacher Training at UIN Sunan Kalijaga is one of the master programs at UIN Sunan Kalijaga Yogyakarta. The Master Program of the Faculty of Tarbiyah and Teacher Training at UIN Sunan Kalijaga has also done various things in order to realize UIN Sunan Kalijaga's goal of becoming a World Class University. One of them is the management of facilities and infrastructure that serves as a learning support.